Influence of Pore Geometry on Sandstone Pore Analysis Based on a Digital Core - Liu, Xuechao; Ren, Dazhong (Frontiers in Physics, 2022)
A digital core obtained without damage and contact can provide intuitive and quantitative analysis data for sandstone pore structure analysis. However, pore analysis results based on digital cores are quite different from experimental results due to limitations of scanning resolution, quality, pore extraction method, and experimental errors. In this research, the influence of pore geometry on pore analysis is studied from pore angles and pore resolution. First, sharp angles are extracted by image processing, and the influence of angles on pore radius distribution is analyzed. Then, by up–down sampling, high- and low-resolution digital cores are reconstructed, and the effects of resolution on pore connectivity and throat structure are discussed.